The sumplokē of the narrating voice in A la recherche du temps perdu. Issue 6 (2nd June 2020) - Dutton, James
ABSTRACT: This article contends with a primary, yet unresolved, problem in Proust criticism: just who is the narrator of A la recherche du temps perdu ? Rather than answering, I seek to de-legitimise the 'who is' of this contention. Applying Derrida's famous critique of ontological presence ( parousia ) and incorporating his notion of iterability offers a reading by which the narrating 'voice' of Proust's fiction disperses across different characters even in the work of a sentence – a possibility invited by Proust's elusive style of narration. Proust's novel in turn foregrounds the instability of subjectivity which is typified by the iterability of language. As language organises to form a text, deconstruction privileges the interstices that work between words and engender context, or restance, and these become the moments of departure and appropriation for any Proustian narrator. In that regard, I argue that Derrida's adoption of the sumplokē (the weaving, or conjunction of being and not-being that renders discourse) aptly describes the fluctuation in and out of appropriated 'self' of the narrat ing Proustian sentence that never fixes a static present, or presence.